Diary of a mad brownie : with supporting documents - Coville, Bruce (Coville, Bruce. Enchanted files., 2015)
"Angus Cairns is a brownie, a magical creature with a fastidious nature. Alex Carhart is the messiest eleven-year-old in the United States of America. Together, this unlikely pair embarks on an unforgettable adventure"--